Strategi Pembentukan Karakter Siswa di SD Muhammadiyah 6 Kecamatan Medan Perjuangan - Imas Ayu Salamah; Nur Dahyanti; Soleh Parlindungan; Sylvi Marsela Diastami; Tri Sucu Apriani Harahap; Maulidayani M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to be able to able to describe and find out about the strategies for character formation of studens at SD Muhammadiyah 6 Kecamatan Medan Perjuangan. In the current era of globalization , the moral crisis has become a very serious and complex problem that needs to be addressed by technological developments the are increasingly fast and sophisticated and easily accessibleto anyone. Even thougt it is like two sides of a knife, without realizing it, the current generation of the Indonesian nation is facing a moral crisis. This needs to be of greater concern to the current govemment, especially for educational institutions. The process of moral formation of the nations generation can be improved and pursued through the education system and emphasis on character formation, althougt the process and result it cannot be seen immediately thet with these efforts, it is hoped that at least the younger generation will be stronger in maintaining good morals in this era of globalization.